Risk-Based Method-Technology Integration on Spun Pile Production for Product and Service Quality - Hidayawanti, Ranti; Latief, Yusuf; Gaspersz, Vincent (Civil Engineering Journal, 2024)
The research aims to identify the risk factors and the medium-high risks to use as the basis for the innovative method of spun pile manufacturing technology. The research uses the Delphi method to analyze and review the validity of content construction, pilot and respondent surveys, focus group discussions, and expert validation. The findings show utilizing and optimizing the technology on production machinery is influential for results on both product and service quality. The dominance category in the medium-risk technology indicates the need for improvement in the operator's competence. The result also indicates the largest medium risk is during the initial integration, Cutting and Heading at 84%, and the final step, Stressing and Spinning, at 59%. The research improvement to map the production process is related to the medium and high risks to know where and how the industry can improve. This risk-based technology and integration method is a proposed method using an approach to innovation management by reducing the risk values. Innovation by improving the standard operational procedure (SOP) was based on the relation of each activity during the integration within the risk category of medium-medium, medium-high, and high-high. We recommend improving SOP and utilizing information technology on precision for both subprocesses. Doi: 10.28991/CEJ-2024-010-11-015 Full Text: PDF